2022
DOI: 10.1186/s12913-022-07789-7
|View full text |Cite
|
Sign up to set email alerts
|

Program evaluation of a pilot mobile developmental outreach clinic for autism spectrum disorder in Ontario

Abstract: Background Autism spectrum disorder (ASD) is a neurodevelopmental disorder with increasing prevalence worldwide. Early identification of ASD through developmental screening is critical for early intervention and improved behavioural outcomes in children. However due to long wait times, delays in diagnosis continue to occur, particularly among minority populations who are faced with existing barriers in access to care. A novel Mobile Developmental Outreach Clinic (M-DOC) was implemented to deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Prior studies have found that although barriers to access health care exist in the GTA and Ontario broadly, when health promotion interventions have been implemented among the general population in the region, they raise awareness and knowledge of health prevention, diseases, and disorders; increase patient use and uptake of health care services; and improve diagnostic pathways [ 78 , 79 , 80 ]. The results from this study however indicate that such interventions are not translating into improved health outcomes for first and second generation South Asian immigrants managing a CID.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have found that although barriers to access health care exist in the GTA and Ontario broadly, when health promotion interventions have been implemented among the general population in the region, they raise awareness and knowledge of health prevention, diseases, and disorders; increase patient use and uptake of health care services; and improve diagnostic pathways [ 78 , 79 , 80 ]. The results from this study however indicate that such interventions are not translating into improved health outcomes for first and second generation South Asian immigrants managing a CID.…”
Section: Discussionmentioning
confidence: 99%